INCREASING ELECTRICITY SAVING IN AUTOMATIC WATER TANDON BASED ON SMART ENHANCE CONTROL SYSTEM - Risky Illahi Reinaldo Yusup; Solly Aryza; Adi Sastra P Tarigan (INFOKUM, 2022)
Efforts to build Indonesia into an electricity-efficient country require a smart system in its control where the government is obliged to present various policies that can unravel various environmental problems with smart and fast concepts. Where in this research designThis automatic faucet control device that can save electricity is made by utilizing a Passive Infrared (PIR) sensor as the control center and detecting objects in the form of human body parts. This PIR sensor will send instructions to the Relay to move the solenoid faucet which functions as a water flow valve.[1] The results of the analysis show that the PIR (Passive Infrared) sensor on this tool can detect objects within a maximum distance of 150 cm meters. When the PIR sensor receives radiation from an object, the solenoid valve opens the valve to drain water. With the automatic faucet control that is used in the men's toilet, it can make it easier for humans because it can be done by an electronic device in the form of a sensor and a controller.